2002
DOI: 10.1677/joe.0.1730063
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in adult rat offspring associated with maternal dietary fat and alcohol consumption

Abstract: Maternal diet during pregnancy has been reported to alter the offspring's ability to respond to a glucose challenge. The current studies report changes in basal and insulinstimulated, in vitro glucose uptake in red (soleus) and white (extensor digitorum longus) muscle fiber types, as well as whole body insulin responsiveness of adult rat offspring associated with their mother's dietary fat and alcohol content during pregnancy.The offspring of Harlan-derived Sprague-Dawley female rats, dosed during pregnancy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 20 publications
7
41
1
Order By: Relevance
“…As found in other IUGR studies (41,53), alcohol-exposed rat offspring have increased expression of the hepatic ratelimiting gluconeogenic enzyme phosphoenolpyruvate carboxykinase (19,68). Thus, an increase in corticosterone levels in alcohol-exposed offspring could provide an explanation for anomalies of glucose homeostasis that we (16 -18) and others (22,46) have previously reported. Collectively, these studies have shown that rat offspring prenatally exposed to alcohol may be born small, but undergo a period of catch-up growth in association with insulin resistance, dyslipidemia, and hyperglycemia.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As found in other IUGR studies (41,53), alcohol-exposed rat offspring have increased expression of the hepatic ratelimiting gluconeogenic enzyme phosphoenolpyruvate carboxykinase (19,68). Thus, an increase in corticosterone levels in alcohol-exposed offspring could provide an explanation for anomalies of glucose homeostasis that we (16 -18) and others (22,46) have previously reported. Collectively, these studies have shown that rat offspring prenatally exposed to alcohol may be born small, but undergo a period of catch-up growth in association with insulin resistance, dyslipidemia, and hyperglycemia.…”
Section: Discussionsupporting
confidence: 74%
“…Aliquots of serum were stored at Ϫ20°C until analysis. Only male offspring were used because in the vast majority of studies of IUGR rats, abnormalities of glucose metabolism were found only in males (22,57). All of the animal studies were approved by the Committee for Animal Care and Use in Research and Teaching of the University of Manitoba.…”
Section: Methodsmentioning
confidence: 99%
“…Feed intake of EtOH-treated dams was Ͻ 10% that of controls, but weight gain during pregnancy, litter size, and perinatal mortality were similar to controls. Our model differs from the model used by Pennington and colleagues (23,48) in that they administered EtOH in a liquid diet, and pups were surrogate fostered to nontreated dams. Cross-fostering is used to prevent a delay in pups' weight gain while suckling from their own undernourished mothers or to study the effects of chronic alcoholism during pregnancy or lactation separately (67).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, three out of seven prepubertal children with FAS had abnormal oral glucose tolerance tests with increased plasma insulin response. We and others have shown that EtOH ingestion during pregnancy in amounts corresponding to human chronic drinking (63,69) can lead to IUGR and is associated with insulin resistance, hyperlipidemia, and glucose intolerance in adult rat offspring (12,13,23,40,48). At the cellular level, these rats have increased intramuscular and intrahepatic triglycerides (14); impaired insulin signaling with reduced muscle protein kinase C activation (15), glucose transporter-4 translocation (12,13), and glucose uptake (23); and increased liver expression of gluconeogenic genes (16,68).…”
mentioning
confidence: 99%
“…To investigate the impact of maternal overnutrtion on the fetus, several studies have used the high-fat diet during pregnancy /lactation. They have shown that exposure to the high fat diet during pregnancy results in altered metabolism in the newborn can also lead to the development of metabolic diseases, including insulin resistance and dysfunction of pancreatic -cells, in the offspring (Elton, Pennington et al 2002;Buckley, Keseru et al 2005;Taylor, McConnell et al 2005). Thus, maternal nutrition directly impacts the developing -islet cells and can program the fetus for insulin resistance as adults.…”
Section: Animal Models For Studying Programming Of the Metabolic Syndmentioning
confidence: 99%